Efektifitas Lagu dalam Pembelajaran Ilmu Nahwu - Damanhuri (el Hakim Press, 2017)
Various efforts from Arabic language teachers to enable learners understand the material and mastering the Arabic language has been taken seriously and sincerely. Learners with a low level of motivation and flogging negative globalization so as to keep the mastery of Arabic, requires teachers and researchers continue diligence to present an attractive and innovative learning approaches either the content or the process approach that includes methods and media learning Arabic. In principle Qowaid learning, that feel heavy by novice learners, should be made fun and not difficult. Examples of the scholars is done by presenting the material with songs nadzam. It is within the framework of fun and not difficult.This study attempted to determine the effectiveness of learning Nahwu Shorof with rhyme and rhythm and how to improve the quality of learning. This study used a qualitative approach to the type of action research Classes (Classroom Action Research). Results of studies using three cycles indicate that the use of the song effectively improve the learning process Nahwu be better.